Transmission of unfolded protein response—a regulator of disease progression, severity, and spread in virus infections - Vibhu Prasad (mBio)
ABSTRACT The unfolded protein response (UPR) is a cell-autonomous stress response aimed at restoring homeostasis due to the accumulation of misfolded proteins in the endoplasmic reticulum (ER). Viruses often hijack the host cell machinery, leading to an accumulation of misfolded proteins in the ER. The cell-autonomous UPR is the immediate response of an infected cell to this stress, aiming to restore normal function by halting protein translation, degrading misfolded proteins, and activating signaling pathways that increase the production of molecular chaperones. The cell-non-autonomous UPR involves the spreading of UPR signals from initially stressed cells to neighboring unstressed cells that lack the stressor. Though viruses are known modulators of cell-autonomous UPR, recent advancements have highlighted that cell-non-autonomous UPR plays a critical role in elucidating how local infections cause systemic effects, thereby contributing to disease symptoms and progression. Additionally, by utilizing cell-non-autonomous UPR, viruses have devised novel strategies to establish a pro-viral state, promoting virus spread. This review discusses examples that have broadened the understanding of the role of UPR in virus infections and disease progression by looking beyond cell-autonomous to non-autonomous processes and mechanistic details of the inducers, spreaders, and receivers of UPR signals.